EKONSTRUKSI PENERAPAN SYARI’AT ISLAM DAN TANTANGAN DEMOKRASI DI INDONESIA - Zulfadli Zulfadli (Turast: Jurnal Penelitian dan Pengabdian, 2015)
This article discusses the reconstruction of the application of Islamic law and the challenges of democracyin Indonesia. In recent years, the application of Shari'ah local regulations both at local and national level.Reformasi Shariah is a necessity. Because Shari'ah plays an important role in any religious activities of humanbeing. Shariah has been seen as something final, must be revisited in order to accommodate the needs of thetimes. Application of Islamic shariah relation to democracy is interesting to study. This study is a library withdescriptive-analytical. The results of this study are the demands of the application of Islamic syar'at that occur invarious areas with formal-legal Shari'ah local regulations need further evaluation and assessment. It is necessaryfor the formulation of the concept of Shari'ah that humanity in accordance with the realities of contemporarysociety by considering democracy, human rights. The rights of non-Muslims, women, freedom of civil society.